Interception of enamine intermediates in reductive functionalization of lactams by sodium hydride: synthesis of 2-cyano-3-iodo piperidines and pyrrolidines - Chen, Jiahua (2022)
Facile conversion of 2-piperidones and 2-pyrrolidones into 2-cyano-3-iodo piperidines or pyrrolidines has been accomplished by the sequence of 1) controlled hydride reduction of lactams using sodium hydride (NaH) in the presence of sodium iodide (NaI); 2) silylation of anionic hemiaminal intermediates to facilitate deoxygenation to form an equilibrium mixture of iminium cations and enamines-silanol pair; 3) interception of enamine intermediates by electrophilic iodination to generate iodonium ions; 4) nucleophilic cyanation of the resultant iminium cations. The overall transformation proceeded in highly diastereoselective fashion. The resultant 2-cyano-3-iodo piperidines were converted into 2-cyanotetrahydropyridines, which could be used for [2 + 2]-annulation or ring-expansion reactions with reactive benzyne or alkyne species, respectively.